Induction of Labor using Misoprostol in a Tertiary Hospital in the Southeast of Brazil - Silva, Tácito Augusto Godoy; Borges Júnior, Luciano Eliziário; Tahan, Luisa Almeida; Costa, Taynná Ferreira Arantes; Magalhães, Fernanda Oliveira; Peixoto, Alberto Borges; Martins, Wellington de Paula; Araujo Júnior, Edward (Revista Brasileira de Ginecologia e Obstetrícia / RBGO Gynecology and Obstetrics, 2017)
Purpose To assess cases of labor induction with vaginal 25-µg tablets of misoprostol and maternal outcomes in a tertiary hospital in southeastern Brazil.Methods This was a retrospective cohort study of 412 pregnant women with indication for labor induction. Labor induction was performed with vaginal 25-µg tablets of misoprostol in pregnant women with Bishop scores < 6. Stepwise regression analysis was used to identify the factors present at the beginning of induction that could be used as predictors of successful labor induction.Results A total of 69% of the pregnant women who underwent labor induction progressed to vaginal delivery, and 31% of the women progressed to cesarean section. One or two misoprostol tablets were used in 244 patients (59.2%). Of the 412 patients, 197 (47.8%) required oxytocin later on in the labor process, after induction with misoprostol. The stepwise regression analysis showed that only Bishop scores of 4 and 5 and previous vaginal delivery were independent factors with statistical significance in the prediction of successful vaginal labor induction (β = 0.23, p < 0.001, for a Bishop score of 4 and 5, and β = 0.22, p < 0.001, for previous vaginal delivery).Conclusion Higher Bishop scores and previous vaginal delivery were the best predictors of successful labor induction with vaginal 25-µg tablets of misoprostol.
Keywords: labor induction; misoprostol; oxytocin; cesarean sections